Estrategias de promoción turística para la potenciación de la Isla Santa Clara en destino ecoturístico. - Caraguay Caraguay, Priscilla Del Carmen (My University, 2019)
The Santa Clara Island Marine Reserve is located northeast of the Jambelí archipelago and it belongs to the Santa Rosa canton. The objective of this research is to identify tourism promotion strategies for the transformation of Santa Clara Island into an ecotourism destination and will also be determined and analyzed. The research method that was applied in this study is the inductive and documentary method. The research instrument that was used is the interview with the tour operators authorized to offer tourist packages to the island to establish the promotion strategies and techniques that will be used for the promotion of the island. The most important terms for the development of this research were conceptualized, such as tourism, tourism promotion and ecotourism destiny, which are the independent and dependent variables respectively to better understand the research content.
La Reserva Marina Isla Santa Clara se encuentra al Noreste del archipiélago de Jambelí y este pertenece al cantón Santa Rosa. El objetivo de esta investigación es identificar las estrategias de promoción turística para la transformación de la isla Santa Clara en destino eco turístico además se las determinara y analizara. El método de investigación que se aplicó en este estudio es el método inductivo y documental. El instrumento de investigación que se utilizo es la entrevista a las operadoras de turismo habilitadas para ofrecer paquetes turísticos hacia la isla para establecer las estrategias y técnicas de promoción que se utilizaran para la promoción de la isla. Se conceptualizo los términos más importantes para el desarrollo de esta investigación como son turismo, promoción turística y destino eco turístico que son las variables independiente y dependiente respectivamente para comprender mejor el contenido de la investigación.
Keywords: RECURSOS; DESTINO; RESERVA MARINA; PROMOCIÓN; ESTRATEGIAS; ECOTURISMO